Perceraian dan Perilaku Sosial Masyarakat Muslim Era Covid19 di Banyuwangi - Irfan Hamdani Ratomi; Subaidi Qomar (Universitas Batanghari Jambi, 2022)
This study aims to determine the factors that cause divorce in Muslim families in Muncar District, Banyuwangi Regency. This study uses a qualitative research method, where the researcher goes directly to the field and talks directly with the informants. Data collection techniques in this study are observation, interviews and documentation. Based on the findings of the data in the field, divorce is caused because between husband and wife do not carry out their functions as a husband and wife that is less responsible. Some of the factors that cause divorce in Muncar District include economic problems, infidelity, disputes, selfish partners, couples often get drunk and do not respect each other. The formation of community behavior that divorce in the Covid-19 era is experiencing adoption, namely events that occur repeatedly which are absorbed by individuals so that they affect the formation of attitudes. Informants who experience divorce certainly have their own trauma about marriage, besides that, the perception of society with individuals who experience divorce tends to be negative because they cannot maintain the ties of marriage they experience. That way, families who experience divorce need moral encouragement to rise from family disorganization.